High concentrations of cellulosic ethanol achieved by fed batch semi simultaneous saccharification and fermentation of waste-paper - Elliston, Adam (Elsevier Applied Science ;, Elsevier Science Pub. Co, 2013)
A fundamental goal of second generation ethanol production is to increase the ethanol concentration to 10% (v/v) or more to optimise distillation costs. Semi simultaneous saccharification and fermentations (SSSF) were conducted at small pilot scale (5 L) utilising fed-batch additions of solid shredded copier paper substrate. Early addition of Accellerase® 1500 at 16 FPU/g substrate and 30 U/g β-glucosidase followed by substrate only batch addition allowed low final equivalent enzyme concentrations to be achieved (3.7 FPU/g substrate) whilst maintaining digestion. Batch addition resulted in a cumulative substrate concentration equivalent to 65% (w/v). This in turn resulted in the production of high concentrations of ethanol (11.6% v/v). The success of this strategy relied on the capacity of the bioreactor to perform high shear mixing as required. Further research into the timing and number of substrate additions could lead to further improvement in overall yields from the 65.5% attained.